Using prevention guidance of common physiological symptoms in pregnancy: a qualitative study - Asih, Fransisca Retno; Danti, Renita Rizkya; Nuristy Brillian Ainindyahsari Winarna (Universitas Aisyiyah Yogyakarta, 2024)
Information about pregnancy is widely accessed by pregnant women, ranging from electronic media, print media, and even social media. One of them is the guide to the prevention of common physiological symptoms in pregnancy (PGCPSP). This guide quantitatively has a very positive impact on the success of preventing pregnancy complaints. However, independent attitudes related to the experience of using this guide have not been measured. The satisfaction and success of pregnant women in using this media is a benchmark for researchers to develop this educational media. This study aims to explore in depth the experiences of pregnant women in preventing and managing pregnancy complaints using the PGCPSP. This research is a qualitative study with a phenomenological approach. Data was collected through in-depth interviews with six pregnant women and four midwives. Participants were selected by purposive sampling. Interviews were recorded, transcribed, translated, and thematically analyzed using NVivo 12 trial version software. We identified three themes and eight sub-themes related to the experience of using PGCPSP: personal condition before using PGCPSP, experience of using PGCPSP, and recommendations for PGCPSP development. Literacy media such as PGCPSP positively impact pregnant women's experiences in overcoming various complaints. Health service providers must develop strategies using educational media. so that pregnant women have the knowledge and foster self-confidence for a satisfying pregnancy experience. In addition, efforts to develop forms of educational media through digital platforms are needed for the development of digital literacy for pregnant women in the future.